The Relative Citation Ratio: A Modern Approach to Assessing Academic Productivity within Plastic Surgery - Christopher James Didzbalis, BA; David Avery Cohen, BA; Isabel Herzog, BA; John Park, PharmD; Joseph Weisberger, MD; Edward S. Lee, MD (Plastic and Reconstructive Surgery, Global Open, 2022)
Background:. The accurate assessment of physician academic productivity is paramount and is frequently included in decisions for promotion and tenure. Current metrics such as h-index have been criticized for being biased toward older researchers and misleading. The relative citation ratio (RCR) is a newer metric that has been demonstrated within other surgical subspecialties to be a superior means of measuring academic productivity. We sought to demonstrate that RCR is a valid means of assessing academic productivity among plastic surgeons, and to determine demographic factors that are associated with higher RCR values. Methods:. All Accreditation Council for Graduate Medical Education-accredited plastic and reconstructive surgery residency programs and faculty throughout the United States were compiled from the American Council of Academic Plastic Surgeons website. Demographic information was obtained for each surgeon via the program’s website, and RCR data were obtained utilizing iCite, a bibliometrics tool provided by the National Institutes of Health. Surgeons were excluded if any demographic or RCR data were unavailable. Results:. A total of 785 academic plastic surgeons were included in this analysis. Surgeons who belonged to departments with more than six members had a higher median RCR (1.23). Increasing academic rank (assistant: 12.27, associate: 24.16, professor: 47.58), chief/chairperson status (47.58), male gender (25.59) and integrated model of residency training program (24.04) were all associated with higher median weighted RCR. Conclusions:. RCR is a valid metric for assessing plastic surgeon academic productivity. Further research is warranted in assessing disparities among different demographics within academic plastic surgery.